The Impact of Cleft Lip/Palate and Surgical Intervention on Adolescent Life Outcomes - Bruce Wydick; Mustafa Zahid; Sam Manning; Jeremiah Maller; Kira Evsanaa; Susann Skjoldhorne; Matthew Bloom; Abhishek Das; Gaurav Deshpande (Ubiquity Press, 2022)
Background: Cleft lip/palate (CLP) is a congenital orofacial anomaly appearing in approximately one in 700 births worldwide. While in high-income countries CLP is normally addressed surgically during infancy, in developing countries CLP is often left unoperated, potentially impacting multiple dimensions of life quality. Previous research has frequently compared CLP outcomes to those of the general population. But because local environmental and genetic factors contribute to the risk of CLP and also may influence life outcomes, such studies may downwardly bias estimates of both CLP status and correction. Objectives: This research represents the first study to use causal econometric methods to estimate the effects of both CLP status and CLP correction on the physical, social, and mental well-being of children. Methods: Data were collected first-hand from 1,118 Indian children, where we obtained first-hand data on height, weight, grip strength, cognitive ability, reading, and math ability. A professional speech therapist reviewed digital recordings of speech taken at the interview to obtain four measures of speech quality. Using this data, the household fixed-effects model we employ jointly estimates effects of CLP status and CLP surgical intervention. Findings: Our results indicate that adolescents with median-level CLP severity show statistically significant losses in indices of speech quality (-1.59σ), physical well-being (0.32σ), academic and cognitive ability (-0.37σ), and social integration (-0.32σ). We find strong evidence that CLP surgery significantly restores speech if performed before five years of age. The first surgeries performed on less-severe CLP cases significantly restore social integration, psychological well-being, academic/cognitive ability, and a general index of human flourishing. Conclusions: Children born with CLP in India face statistically significant losses in speech, physical health, mental health, and social inclusion. CLP surgical intervention significantly restores speech quality if carried out at an early age. Surgeries with the most significant impact on life outcomes are the first surgeries performed on less-severe CLP cases.